The anodic oxidation of thiocyanate ion dissolved as KSCN in dimethylsulphoxide - Martínez, C. (1972)
The anodic oxidation of SCN- ion dissolved as KSCN in dimethylsulphoxide, on platinum electrodes, was investigated at cu 25,60 and 160°C by means of various non-stationary electrochemical techniques. At low temperatures one anodic and two main cathodic processes were found. The anodic oxidation of SCN- ion yields as primary product the SCN radical, which readily produces (SCN)*. The latter can be in part reduced back to SCN- ion, because it reacts in part yielding solvated hydrogen ions which cause the second cathodic reaction. In the region of 60”C, no (SCN), cathodic current is observed. In the region of 160°C the only reaction is SCN- ion oxidation and the primary product polymerizes to (SCN)., which forms a film on the electrode, causing passivation. On the basis of kinetic data obtained for the different reactions, a mechanism for the anodic oxidation of the SCN- ion and for the passivating film formation is suggested. The second process only partly fits the Mtlller model for the electrochemical growth of insoluble layers.